ANALISA HUBUNGAN KAUSALITAS ANTARA PERTUMBUHAN EKONOMI, NERACA PERDAGANGAN, DAN NILAI TUKAR RUPIAH - Martha Carolina; Ade Nurul Aida (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2016)
This research is intended to examine the relationship between economic growth, trade balance and exchange rate. This type of research is a descriptive research with quantitative approach. Determination of the sample is based on time series data for a period of 30 years ranges from 1985 to 2015 period by using saturation sampling method, as many as 29 samples. This research was conducted by using secondary data, such as the Indonesian currency exchange rate against the US dollar published by BI and GDP data published by BPS. Based on Granger Causality Test, this result has shown that there is a significant positive correlation between economic growth and exchange rate, there was no positive correlation a significantly between economic growth and net exports, and there was no positive correlation significantly between net exports and exchange rate.